Blockchain Traceability and Consumer Willingness-to-Pay (WTP): Behind the Construction of Transparency Index (TRPI) - Sciortino, Caterina; Sgroi, Filippo; Modica, Federico (Research on World Agricultural Economy, 2026)
This paper examines how consumers perceive and value blockchain-based traceability when food products are associated with health, quality, and sustainability claims. In markets where added value is increasingly communicated through transparency, safety, and authenticity cues, blockchain can act as a supporting tool rather than as a standalone innovation. Survey evidence shows that consumers clearly distinguish between search, experience, and credence attributes, and that willingness to pay for digitally certified products is mainly driven by credence-related concerns such as food safety, fraud prevention, transparency, and sustainability. To capture these attitudes, a Transparency Index (TRPI) is developed by combining perceptions of authenticity, ethical and environmental motivations, and trust in digital certification systems. Consumers who place greater importance on these aspects display a higher acceptance of blockchain-verified products, while standard socio-demographic characteristics explain only a limited share of variation in willingness to pay. The results indicate that blockchain mainly reinforces existing consumer expectations regarding product credibility rather than creating new demand. This is particularly relevant for value-added food markets such as functional, clean-label, allergen-free, and sustainability-oriented products, where trust in production processes and information reliability is essential. The findings suggest that blockchain-based traceability is most effective when combined with established certification schemes, as it strengthens transparency and credibility along the supply chain. By improving access to information on production practices and environmental performance, blockchain can also support consumer valuation of carbon-related attributes, making CO₂ reduction efforts more credible and economically relevant in agri-food markets. ER